Implementation of Early Warning System (EWS) by Nurses in the Emergency Department and the Impact to Prevention Incident No Expected: Systematic Review - Rio Verdiansyah; Hening Pujasari; Hanny Handiyani; Tuti Afriani (Indonesian Journal of Global Health Research, 2025)
The Emergency Department is a high-intensity clinical setting that manages critically ill patients who are highly susceptible to sudden clinical deterioration. Early detection through the implementation of the Early Warning System plays a crucial role in preventing unexpected adverse events, with nurses serving as the primary implementers of this system. This review aims to evaluate current evidence on the implementation of the Early Warning System by nurses in the Emergency Department and its impact on the prevention of unexpected adverse events. This study employed a systematic review approach by applying the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines during the article selection process and using the 2023 edition of the Joanna Briggs Institute (JBI) Critical Appraisal Tool to assess the quality of included studies. Search for articles through the ScienceDirect, ProQuest, PubMed, BMJ Journal, and EBSCO databases from 2020 to 2025. and 10 articles were analyzed. The majority of studies reported that the use of the Early Warning System consistently enhances the early detection of patient deterioration, accelerates clinical response, improves triage accuracy, and assists in predicting the need for advanced care such as admission to intensive care units. Implementation by nurses was also associated with improved compliance in vital signs monitoring and a reduction in patient mortality.